(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
There search aimed to determine the dimensions of strategic monitoring and its role in achieving sustainable competitive advantage The research problem was based on the fact that insurance companies face many challenges due to the changing dynamic environment in which they operate. The research adopted the questionnaire as a tool for collecting data from members of the Iraqi insurance company ( senior management ) and it was distributed (75) questionnaires were retrieved, and (60) were retrieved, capable of statistical analysis, as the statistical program (SPSS V.26) was used to calculate arithmetic mean, standard deviation, relative importance, cronbach s alpha, T-test person correlation coefficient, coefficient of determination R2, The most prominent findings of the research demonstrate the importance of strategic monitoring in the positive impact it has on sustainable compete advantage and ribute to strengthening internal and external partnerships to benefit from the expertise and experience of others and to stimulate competition among employees to motivate them to achieve